(untitled) (diségno, 2019)
The paper deals with the morphologic and urban analysis of Bressanone through the digital modeling of the territory and the building layout with the aim of defining a mode of observation from the landscape to the city, able to provide the tools for the knowledge of the historical and architectural heritage of Bressanone, through the elaboration of new images. The symbolic values, given back by the images produced, decline the orographic and urban complexity in the language of representation, which translates the analytical process into a digital iconographic apparatus. The views realised from the 16th century onwards are integrated with the new graphic elaborations, tracing the spatial relationships of the territorial and building fabric.